Cinema, educação e filosofia: possibilidades de uma poética no ensino - Angerami, Paula Linhares [UNESP] (2014)
Cinema has been used in education, although in an instrumental way, as a didactic resource to reach a previously determined educational aim. This research will analyze the possibility of utilizing for education the esthetic qualities provided by cinema. Specifically, I will explore the possibility of teachers using selected films to provide to students a unique visual and auditory opportunity to observe and discuss a particular qualitative and reflective experience, along the lines recommended by Dewey. In order to accomplish this, I will discuss cinema as a component of the poetic of education, approaching the intellectual, moral, esthetical and ethical aspects of human beings. In that perspective, through the hermeneutic method, I will analyze and conceptualize esthetic, qualitative experience and reflective thought using Dewey as a reference. Following this, I will discuss in depth the concept cinema The expected result is to verify the potentiality of cinema to provide a first quality qualitative and reflective experience about ethic’s questions.